Umbilical cord blood units for public storage donors screening for markers of infectious agents - A. B. Smolyaninov; O. G. Hurcilava; D. A. Ivolgin; O. V. Supilnikova; A. S. Khrupina (Журнал инфектологии, 2014)
The screening of 3515 cord blood samples which had entered bank for public use for presence of markers of infectious agents was carried out. It was established that majority of cord blood units contain markers of cytomegalovirus and Toxoplasma (81%) that is not a contraindication for storage and subsequent use of these samples. In 4.6% of cases umbilical cord blood units were subjected to disposal because of identification of viral hepatitis B and C, as well as Tr. pallidum markers, moreover, the largest share of the discarded units contained antibodies to HbscorAg – 71,3%. Inclusion of analysis on the presence of Anti-HBcor in the required laboratory screening of mothers-donors CB was proposed in order to reduce the percentage of discarded umbilical cord blood units for the public inventory.